AVALIAÇÃO DO EFEITO DO ESTRES HIDRICO EM CULTIVARES DE TRIGO EM SOLO DO CERRADO-MATO-GROSENSE - Maas, Adriano; González Aguilera , Jorge; de Freitas Lima, Gabriel; Freitas de Souza , Beatriz; Gabriel Schirmann Bronstrup , Lamayson (ANAIS DO ENIC, 2026)
-